Manfaat Kebiasaan Pola Makan Menurut Prinsip Islam Halalan Tayyiban - Intan Kurniasari; Kayla Faiza Wijaya; Larasati Khairunissa Rahman (Journal of Creative Student Research, 2023)
There are various types of eating patterns nowadays. This article will discuss one variation of the diet, namely the Islamic diet which has the halalan thayyiban principle. halal means what is permitted while thayyib means what is good. This article also includes foods recommended in Islam, and how these foods can benefit the human body. Halal and thayyib principles also emphasize the process, from taking raw materials to distribution. One of the important processes in food processing is slaughter, there are certain provisions in Islam. This eating pattern also emphasizes adequate eating and appreciating eating, by saying bismillah before eating. Muslims are advised to eat in moderation, eat when hungry and stop eating before they are full. this practice can make eating better. This article also contains scientific research regarding the application of halal and thayyib principles and their relationship to health, such as the link between excessive use of additives, which are not in accordance with thayyib principles, with intestinal infectious diseases.